Early athletic identity formation and development: perceptions of elite Gaelic athletes - Geary, M.; Kitching, N.; Campbell, M.; Houghton, F. (Sports, 2025)
Background/Objectives Athletic identity (AI) is an important part of an elite athlete`s self-concept and can positively impact sports performance, but over-emphasis can lead to potentially negative outcomes. Identity theory suggests that identity is shaped by individuals` roles, group affiliations, self-perceptions, and important changes in personal circumstances. Athlete transitions are changes that occur in an athletes` athletic and/or non-athletic circumstances, which can impact identity development. Using identity theory, this study aimed to explore the athletic transitions important in early AI formation and development in elite Gaelic athletes.